Utility of single fiber electromyography in the diagnostic evaluation of patients with isolated ocular symptoms - (:unkn) unknown (My University, 2022)
Background and aims: Ptosis and diplopia are frequent presentation symptoms in the emergency rooms, ophthalmology and neurology clinics. Most of these cases are referred for single fiber electromyographic (SFEMG) examination to confirm or rule out ocular myasthenia gravis (OMG). The aim of this study is to investigate the clinical utility of SFEMG in the assessment of patients with ocular symptoms and signs. Methods: The clinical and electrophysiological data of patients with isolated ocular symptoms, who were referred for SFEMG/jitter analysis to our laboratory for the last 3 years, were retrospectively reviewed. Results: A total of 122 cases (78 female, 44 male) were included in the study. In retrospective review of the followup charts, 62.3% of them were found to have nonmyasthenic disorders. Only 37.7% of the patients had the final diagnosis of OMG. The presence of both ptosis and diplopia, diurnal fluctuation and alternating patern were more likely to be indicative of OMG (p<0,001). SFEMG test was found to have a sensitivity of 80,4%, specificity of 90,8%, positive predictive value of 84.1%, and negative predictive value of 88.5%. Conclusion: This study confirms the diagnostic utility of SFEMG in OMG, in concordance with the literature. However, it draws attention to the overutilization of the test and frequent misdiagnosis of OMG in clinical practice. Disclosure: Authors have no financial disclosure.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)